Formulation and evaluation of theophylline sustained release matrix tablets using synthetic polymers - Navdeep Kaur; Mohit Kumar (Creative Pharma Assent, 2022)
The aim of present work was to develop theophylline sustained release tablets which could improve patient compliance towards the effective management of asthma The polymers, HPMC (Hydroxy propyl methyl cellulose) K4M, HPMC K100M, Eudragit, Chitosan in blending and granulation stage of processing and evaluate their physico-chemical properties. The precompression limits of the powder blends used for the preparation of sustained-release tablets were in an acceptable range of pharmacopeial specification with excellent flow and good compressibility. Wet granulation method prepared tablets using different grades of polymers HPMC K100, HPMC K4M, Eudragit, Chitosan. The active ingredient, release retardants, diluents, fraction of polymer are mixed to make wet mass for granulation. The in- vitro release was prolonged to 12 hours using HPMC K4M, HPMC K100M, Chitosan, Eudragit. F9 formulation prolonged the theophylline release in 12 hours. The effect of polymer on drug release was studied. Thus, sustained release matrix tablets can promise better patient compliance through reduction in over-all dose and dosage regimen, which can be of excessive support to treat chronic disease.